Corporate Investment and Corporate Performance: Do Crisis Matter? - Widarwati, Estu; Nugraha, Muhamad Mugi; Nurmalasari, Nunik; E. Wityasminingsih, E. Wityasminingsih (Jurnal Kajian Akuntansi, 2023)
Corporate performance is an achievement of success from a series of corporate activities in several predetermined strategies. Investing in goods and capital increases the firm's value and therefore the firm's performance will be different during the economic crisis and normal conditions. The study aims to examine the relationship between corporate investment and corporate performance. Furthermore, this study also does a different test of the corporate investment effect on corporate performance between the normal and crisis periods. We use the Capital Expenditure and Net Working Capital as measurements of corporate investment and firm performance proxied by operating profit margin. The sample used are 243 non-financial industries firms listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period, then there is 1215 observation data. The data were analyzed descriptively, and then panel data regression was used for testing the hypotheses. The results showed that the company's investment had a positive effect on the company's performance and there was a significant difference in these influences in both normal and crises periods. This finding has implications that companies can continue investing to improve their performance with economic growth as main consideration for investment decision-making.